Just the tip of the iceberg: uncovering a hyperdiverse clade of African Russula (Basidiomycota, Russulales, Russulaceae) species with signs of evolutionary habitat adaptations - Cathrin Manz; Mario Amalfi; Bart Buyck; Felix Hampe; Nourou S. Yorou; Slavomír Adamčík; Meike Piepenbring (IMA Fungus)
The diversity within the ectomycorrhizal genus Russula (Basidiomycota) in West Africa is largely unexplored. The study area was Benin, where only ten out of the 159 species endemic to tropical Africa have been previously reported. We focused on “Afrovirescentinae”, which is a monophyletic lineage within Russula subgen. Heterophyllidiae sister to subsect. Virescentinae. The phylogenetic placement of this clade was analysed using sequence data from ITS, LSU, mtSSU, tef1, rpb1 and rpb2 regions. Ten “Afrovirescentinae” species are recognised, described and illustrated from Benin. Four of them, R. carmesina, R. hiemisilvae, R. inflata and R. sublaevis, were previously published. Five species, Russula acrialbida sp. nov., R. beenkenii sp. nov., R. coronata sp. nov., R. florae sp. nov. and R. spectabilis sp. nov., are newly described. Species within this group are characterised by densely reticulated spore ornamentation, but they exhibit considerable variation in field appearance and pileipellis structure. In gallery forests, their basidiomata are ephemeral, small and their basidiospores have prominent ornamentation; while in savannah woodlands, the basidiomata are fleshy, large and basidiospores present low ornamentation. We suggest that these morphological traits may represent evolutionary adaptations to a specific environmental condition. We analysed the species richness, ecological range and distribution of the “Afrovirescentinae” clade globally based on data from the UNITE database, estimating a total diversity of 94 species primarily distributed in sub-Saharan Africa, but also in the Neotropics. Four additional previously described species not detected in Benin were assigned to this clade, based on holotype sequencing. Several species are widely distributed across tropical Africa and do not show specificity regarding their associated plant symbionts.